2016
DOI: 10.1111/jpi.12341
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin inhibits tumorigenicity of glioblastoma stem‐like cells via the AKT–EZH2–STAT3 signaling axis

Abstract: Glioblastoma stem-like cells (GSCs) displaying self-renewing and tumor-propagating capacity play a particularly important role in maintaining tumor growth, therapeutic resistance, and tumor recurrence. Therefore, new therapeutic strategies focusing on impairing GSC maintenance are urgently needed. Here, we used GSCs isolated from surgical specimens from patients with glioblastoma multiforme (GBM) to study the roles and underlying mechanisms associated with melatonin in GSC biology. The results showed that mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 49 publications
4
93
0
Order By: Relevance
“…This analysis revealed that the downregulation of CD133 by melatonin was interrupted by blockade of the melatonin membrane receptors. The data further suggested an inhibitory effect of melatonin on GSC self-renewal and tumor-initiating capacity [17].…”
Section: The Impact Of Melatonin On Tumor Stem Cells Melatonin Inhibimentioning
confidence: 82%
See 2 more Smart Citations
“…This analysis revealed that the downregulation of CD133 by melatonin was interrupted by blockade of the melatonin membrane receptors. The data further suggested an inhibitory effect of melatonin on GSC self-renewal and tumor-initiating capacity [17].…”
Section: The Impact Of Melatonin On Tumor Stem Cells Melatonin Inhibimentioning
confidence: 82%
“…Chen and colleagues utilized glioblastoma stem-like cells (GSCs) isolated from surgical specimens of patients with GBM to analyze the role and underlying mechanisms associated with melatonin in GSC biology [17]. They noticed that treatment with 1 mol/L melatonin changed the shape of neurospheres.…”
Section: The Impact Of Melatonin On Tumor Stem Cells Melatonin Inhibimentioning
confidence: 99%
See 1 more Smart Citation
“…Within hours of surgical removal, glioma specimens were enzymatically dissociated into single cells as described previously (26). For short-term in vitro expansion of GSCs, cells were cultured in Neurobasal medium (Thermo Scientific) with N2 and B27 supplements (Invitrogen), human recombinant basic fibroblast growth factor, and EGF (10 ng/mL each; Invitrogen).…”
Section: Lentiviral Short Hairpin Rna-mediated Knockdownmentioning
confidence: 99%
“…Intracranial transplantation of GSCs into nude mice was performed as described previously (26). Briefly, 36 hours after lentiviral infection, live cells were counted and implanted into the right frontal lobes of athymic nude mice.…”
Section: Intracranial Tumor Assaymentioning
confidence: 99%